Changes in body composition by age and obesity status in preschool-aged children: the STEPS study - Tuija Leskinen; Aino-Maija Eloranta; Tuomo Tompuri; Antti Saari; Helena Ollila; Johanna Mäkelä; Harri Niinikoski; Hanna Lagström (NATURE PUBLISHING GROUP, 2022)
Background/Objectives: Obesity in early childhood is associated with increased risk of chronic diseases, but studies of body composition at preschool ages are sparse. Therefore, we examined differences in body composition by sex and obesity status in Finnish preschool-aged children and within-individual changes in body composition in normal and overweight children.
Subject/Methods: Body composition was measured using segmental multifrequency bioimpedance analysis (BIA) in 476 children and in 781 children at age 3 and 5 years, respectively. Of those, 308 had repeated BIA measurements at both ages. BMI-SDS was used for classification of normal weight and overweight children.
Results: Sex difference in the amount of lean mass (LM) was already seen at 3 years of age (boys 11.7 kg, girls 11.3 kg; p < 0.001). At 5 years of age, boys had lower fat mass (FM; 3.6 kg vs. 3.9 kg, p < 0.001), lower percent fat mass (%FM; 17.2% vs. 19.1%; p < 0.001), and higher LM (16.0 kg vs. 15.2 kg; p < 0.001) than girls. Overweight children had higher values in FM, %FM, and LM compared with normal weight peers at both ages. Among normal weight children, the increase of LM by age was associated with only minor changes in FM, whereas children who were or became overweight both LM and FM was substantially increased between 3 and 5 years of age.
Conclusions: BIA-assessed body composition differs by sex and obesity status already at age of 3 years. For children who are or become overweight at very young age, the patterns for the changes in LM and FM by age are different than for normal weight children.